Preparedness of Elementary School Parents for Offline Learning Decisions during the COVID-19 Pandemic - Hariati, Suni; Andriani, Andriani; Nurmaulid, Nurmaulid; Erfina, Erfina; Kadar, Kusrini Semarwati (Jurnal Keperawatan Soedirman, 2023)
Reopening schools during the COVID-19 pandemic requires the full consideration of parents’ decisions due to the worry of exposure for their children. This study evaluated parents’ preparedness for offline learning decisions among elementary school children during the COVID-19 pandemic. This is a cross-sectional study with 134 parents as respondents. The consecutive sampling technique was used. The online questionnaire was distributed on social media to collect data from various regions in Indonesia. The finding indicated that 99 (73%) parents sent their children for offline learning from July to November 2021 for one to three times a week (44.8%) and one to three hours a day (46.8%). The significant factor for parents’ decisions was school preparedness for COVID-19 prevention (p < 0.05). However, parents' preparedness for self-protection and the child's mental condition had no significant relationship because almost all parents were already prepared for these factors (> 95%). Therefore, the government and primary health care have a vital role in supervising and providing a safe environment for children during the COVID-19 pandemic.